The contributions of Imam Shafi'i in Arabic language and literature - Najihah, Abd Wahid; Anas, Mohd Yunus; Nor Hafizah, Abdullah (Medwell Journals, 2016)
The purpose of this working study is to see the extent of experience and education of Imam Shafie in Arabic language and literature. General Muslim public knows Imam Shafie as a great figure in the school of Islamic Law and Jurisprudence. However, it may be rarely known about the early education history of Imam Shafie that focused on learning Arabic language and literature. Hence, with the application of qualitative approach and historical design analysis on the background and history of his life, this study makes an attempt to explain the early experience and learning of Imam Shafie in Arabic language and literature. This study also tries to see how he was recognized as the figure of Arabic language and literature of his time, apart from the figures in the school of Islamic Law and Jurisprudence. The outcome of the analysis found that Imam Shafie received an early exposure in Arabic language education and literature during his childhood until teenager and he was chosen as a transcendent figure of Arabic language and literature at his early teens.